2012
DOI: 10.1108/17597511311316964
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting international doctoral students' academic engagement, satisfaction with their studies, and dropping out

Abstract: Purpose -This article's purpose is to report the findings and implications of a study that explored factors promoting and hindering international doctoral students' academic engagement. Design/methodology/approach -An empirical study sought data through a questionnaire from international students registered for doctoral study at the University of Helsinki. Open-ended and Likert-scale survey data were qualitatively and quantitatively analysed. Findings -The students commented most frequently (41 per cent) on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 36 publications
3
35
0
Order By: Relevance
“…The desire to become a skilled scholar, time investment and positioning oneself as a doctoral student in relation to the local academic context were informed by participants' professional orientations, motivations, and self-monitoring. This supports the finding that emotional aspects, like self-discipline, motivation, and interest, promote, rather than hinder, international doctoral students' studies (Sakurai et al 2012). Contrary to Pyhältö et al (2012b), who identified motivation and selfregulation in doctoral students as problems in general work processes that are rather difficult to solve, the findings of the present study suggest that international doctoral students in Education were very determined, and the positive outlook on stress as a motivator helped orient themselves in terms of learning, role, interests.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…The desire to become a skilled scholar, time investment and positioning oneself as a doctoral student in relation to the local academic context were informed by participants' professional orientations, motivations, and self-monitoring. This supports the finding that emotional aspects, like self-discipline, motivation, and interest, promote, rather than hinder, international doctoral students' studies (Sakurai et al 2012). Contrary to Pyhältö et al (2012b), who identified motivation and selfregulation in doctoral students as problems in general work processes that are rather difficult to solve, the findings of the present study suggest that international doctoral students in Education were very determined, and the positive outlook on stress as a motivator helped orient themselves in terms of learning, role, interests.…”
Section: Discussionsupporting
confidence: 84%
“…The way participants understood themselves as professional subjects (Eteläpelto et al 2014) drew on professional aspirations and interests (Cotterall 2015) and used internal resources (Anderson 2017;Evans and Stevenson 2010;Pyhältö et al 2012b) helped regard stress as a motivational force in their studies. International doctoral students' high motivation, at least initially, has been seen in their proactive involvement in study abroad (Sakurai et al 2012;Zhao et al 2005), while active strategies on the part of doctoral students have been associated with reduced burn-out risk (Stubb et al 2012). Despite the optimistic view of stress participants seemed to share, the choice for it to be treated as a constructive element indicates the need to foster international doctoral students' persistence in the long run.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Needless to say, the doctoral study is a demanding, even nervewracking journey (Gardner, 2007;Walsh, 2010). At times, the attrition rate for doctoral students is a cause for concern demanding further attention (Sakurai, et al, 2012;Trafford & Leshem, 2009;Wright, 2003).…”
Section: International Phd As a Complex Endeavourmentioning
confidence: 99%
“…This existing dichotomy helps explain the reasoning behind the challenges related to linguistic and cultural adjustment and also for the reported sense of isolation, strangeness, loneliness, 'foreignness' and alienation customarily experienced by international students (Fischbacher-Smith et al, 2015;Fotovatian, 2012;He, 2002;Sakurai, Pyhältö, & Lindblom-Ylänne, 2012;Smith & Khawaja, 2011;Walsh, 2010). As a case in point, Sawir and her colleagues (2008, p. 148) undertook a major study of international student security and reported different facets of loneliness: personal, social and cultural.…”
Section: Theoretical Frameworkmentioning
confidence: 99%